Employment and earnings by gender in Mexico: Its relationship with task-biased technological change - Rodríguez Pérez, Reyna Elizabeth; Meza González, Liliana (Estudios Económicos de El Colegio de México, 2021)
To understand how employment and earnings by gender in Mexico are related to task-biased technological change, we analyze changes in employment by occupations defined by the tasks they perform. We also decompose the gender wage gap using the unconditional quantile regressionmethod. The results indicate that the female labor market is polarizing and that the gender wage gap has fallen, but mostly within those occupations involving non-routine cognitivework. These changes have caused the gender wage gap to drop mainly in the upper part of the wage distribution, benefitting women with the highest levels of human capital.